2020
DOI: 10.2147/ijn.s268372
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electrochemical Deposition of Nanostructured Hydroxyapatite Coating on Titanium with Enhanced Early Stage Osteogenic Activity and Osseointegration</p>

Abstract: Purpose The aim of research is to fabricate nanostructured hydroxyapatite (HA) coatings on the titanium via electrochemical deposition (ED). Additionally, the biological properties of the ED-produced HA (EDHA) coatings with a plate-like nanostructure were evaluated in vitro and in vivo by undertaking comparisons with those prepared by acid/alkali (AA) treatment and by plasma spray-produced HA (PSHA) nanotopography-free coatings. Materials and Methods Nanoplate-like HA c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 70 publications
(49 reference statements)
1
24
0
2
Order By: Relevance
“…Electrochemical deposition 24,25 The metal matrix is immersed in the aqueous solution containing the gold-plated ions, and the direct current is passed through to make the positive ions discharge on the surface of the cathode to obtain the metal lm Low dissolution rate; effective Low fatigue strength, poor adhesion between coating and implant Sol-gel method 26,27 The use of metal inorganic salts or metal alcohol salts in water or alcohol solvent hydrolysis or alcoholysis reaction, the formation of the sol through drying dehydration into gel, and then aer heat treatment to obtain the product Uniform layers; the preparation process is easy to control; low processing temperature Fabrication steps; environmentally unfriendly; debonding of the coating layer Plasma spraying 17,28 A kind of gas is ionized by nontransfer arc to form a high temperature plasma jet, and the powder is introduced into it, and the jet is accelerated and impinges on the surface of the substrate to form a coating Effective, lower possibility of coating degradation, Nonuniform coatings, poor adhesion between coating and implants; high dissolution rate; the preparation temperature is too high to make HA decomposition Magnetron sputtering 29,30 It uses charged particles to bombard the target surface in vacuum, and the particles are deposited on the surface of the cold metal substrate to form a coating structure Effective; high purity of layers; ability to coat implants with complex shapes; strong adhesion of lms; dense and uniform coatings Technical complexity; high costs; the subsequent heat treatment is needed to restore the crystalline state of the coating structure, and the high temperature treatment will destroy the HA lattice to some extent Selective laser melting 31,32 This technique uses metal powder to be completely melted under the heat of a laser beam, then cooled and formed coatings Good mechanical property; a high degree of processing freedom…”
Section: Technical Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical deposition 24,25 The metal matrix is immersed in the aqueous solution containing the gold-plated ions, and the direct current is passed through to make the positive ions discharge on the surface of the cathode to obtain the metal lm Low dissolution rate; effective Low fatigue strength, poor adhesion between coating and implant Sol-gel method 26,27 The use of metal inorganic salts or metal alcohol salts in water or alcohol solvent hydrolysis or alcoholysis reaction, the formation of the sol through drying dehydration into gel, and then aer heat treatment to obtain the product Uniform layers; the preparation process is easy to control; low processing temperature Fabrication steps; environmentally unfriendly; debonding of the coating layer Plasma spraying 17,28 A kind of gas is ionized by nontransfer arc to form a high temperature plasma jet, and the powder is introduced into it, and the jet is accelerated and impinges on the surface of the substrate to form a coating Effective, lower possibility of coating degradation, Nonuniform coatings, poor adhesion between coating and implants; high dissolution rate; the preparation temperature is too high to make HA decomposition Magnetron sputtering 29,30 It uses charged particles to bombard the target surface in vacuum, and the particles are deposited on the surface of the cold metal substrate to form a coating structure Effective; high purity of layers; ability to coat implants with complex shapes; strong adhesion of lms; dense and uniform coatings Technical complexity; high costs; the subsequent heat treatment is needed to restore the crystalline state of the coating structure, and the high temperature treatment will destroy the HA lattice to some extent Selective laser melting 31,32 This technique uses metal powder to be completely melted under the heat of a laser beam, then cooled and formed coatings Good mechanical property; a high degree of processing freedom…”
Section: Technical Complexitymentioning
confidence: 99%
“…17 The performances of different surface modication techniques used for the incorporation of metallic ions are summarized in Table 2. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In this paper, we review the adverse effects of metal ions on osseointegration and highlight the emerging applications for metal elements in improving the performance of dental implants.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical deposition (ED) is a common technique for the fabrication of metal substrates, which has the promising advantage of a relatively simple and cost-effective process ( Fathyunes and Khalil-Allafi, 2018 ; Lu et al, 2020 ). Furthermore, the influence of thermal stress on bioimplants can be avoided since the ED process is performed primarily at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, this type of rough surface has random and uncontrolled microstructures, while proteins and cells interact with the implant surface at the nanoscale. It has recently been shown that nanostructures on Ti implants produced by electropolishing significantly enhance the adhesion and osteoblastic differentiation of mesenchymal stem cells ( Lausmaa, 1996 ; Harris et al, 2007 ; Lu et al, 2020 ). Nevertheless, the in vivo environment triggers the release of metal ions from the implant and then initiates malfunction of joint replacements and even toxic effects in the serum.…”
Section: Introductionmentioning
confidence: 99%